Multilayer control of networked cyber-physical systems : application to monitoring, autonomous and robot systems - Manfredi, Sabato (Advances in industrial control., 2019)
This book faces the interdisciplinary challenge of formulating performance-assessing design approaches for networked cyber-physical systems (NCPSs). Its novel distributed multilayer cooperative control deals simultaneously with communication-network and control performance required for the network and application layers of an NCPS respectively. Practically, it distributes the computational burden among different devices, which act cooperatively to achieve NCPS goals. The approach can be applied to NCPSs based on both wired and wireless technologies and so is suitable for future network infrastructures in which different protocols and technologies coexist. The book reports realistic results from performance evaluation of the new approach, when applied in different operative scenarios. Readers of this book will benefit by: learning a general, technology-independent methodology for the design and implementation of cooperative distributed algorithms for flow control at the network layer of an NCPS that gives algorithm-parameter-tuning guidelines for assessing the desired quality of service performance; learning a general methodology for the design and implementation of consensus-based algorithms at the application layer that allows monitoring and control of distributed physical systems and gives algorithm-parameter-tuning guidelines for assessing the desired control system performance; understanding the main network simulators needed to validate the effectiveness of the proposed multilayer control approach in different realistic network operation scenarios; and practising with a cooperative multilayer control project that assesses acceptable NCPS performance in networked monitoring and robot systems, autonomous and queuing networks, and other critical human relief applications. Researchers, graduate students and practitioners working in automation, engineering, sensor networks, mobile robotics and computer networks will find this book instructive. It will also be helpful to network administrators and technicians implementing application-layer and network-layer solutions or installing, configuring or troubleshooting network and control system components of NCPSs.